The Hidden Link: Vitamin D Deficiency and Its Association with Anemia and Red Blood Cell Health in Pregnancy - Mishra, Chandrakesh; Rachna, Rachna; Singh, Shivani; Verma, Juhi; Kulshrestha, Rupita; Kulshrestha, Rupita; Kulshrestha, Manish Raj (Journal of Neonatal Surgery, 2025)
Background: Vitamin D deficiency and anemia are common comorbidities in pregnancy, both independently linked with adverse maternal and fetal outcomes. However, the interrelationship between maternal vitamin D status and hematological health, particularly red blood cell indices, remains incompletely understood. Objective: This study aimed to investigate the association between maternal vitamin D deficiency and anemia, with a specific focus on evaluating the impact of vitamin D status on red cell parameters among pregnant women. Methods: A cross-sectional analysis was conducted involving 150 anemic and 150 non-anemic pregnant women. Serum vitamin D and comprehensive hematological indices—including hemoglobin, red blood cell (RBC) count, hematocrit, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW), and platelet count—were measured and compared between groups. Correlation analyses explored the relationship between vitamin D and red cell indices. Results: Anemic women exhibited significantly lower mean vitamin D levels (9.6 ± 5.0 ng/ml) compared to non-anemic women (29.4 ± 6.0 ng/ml; p < 0.001). All major hematological indices (hemoglobin, RBC, hematocrit, MCV, MCH, MCHC) were reduced, while RDW was elevated in the anemic group (all p < 0.001). Vitamin D levels positively correlated with hemoglobin (r = 0.65), RBC (r = 0.62), and red cell indices, and inversely with RDW (r = –0.51; each p < 0.05). Conclusion: Vitamin D deficiency is strongly associated with anemia and impaired red cell health in pregnancy. Integrating vitamin D screening and supplementation into antenatal care may reduce the burden of gestational anemia and improve maternal outcomes.